2013
DOI: 10.1038/eye.2012.286
|View full text |Cite
|
Sign up to set email alerts
|

A method for the prescription of inexpensive spectacles by non-specialist healthcare workers: S-Glasses

Abstract: Purpose Globally, 153 million people are visually impaired from uncorrected refractive error. The aim of this research was to verify a method whereby autorefractors could be used by non-specialist health-workers to prescribe spectacles, which used a small stock of preformed lenses that fit frames with standardised apertures. These spectacles were named S-Glasses (Smart Glasses). Patients and methods This prospective, single-cohort exploratory study enrolled 53 patients with 94 eligible eyes having uncorrected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Our data identified that older Indigenous Australians and those residing in outer regional locations may benefit the most from focussed resource allocation. There is real‐world evidence that spherical equivalent correction (only) derived from an auto‐refractor can be effective for correcting patients with low degrees of astigmatism . While we acknowledge this is not optimal, given close to 70% of Indigenous participants with severe uncorrected refractive error had a cylinder equal to or less than 1 dioptre, there may be a case for spherical lenses that fit frames with standardised apertures to be stocked in Aboriginal Health Services in the most inaccessible regions of Australia and health workers could dispense spectacles using auto‐refraction results.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our data identified that older Indigenous Australians and those residing in outer regional locations may benefit the most from focussed resource allocation. There is real‐world evidence that spherical equivalent correction (only) derived from an auto‐refractor can be effective for correcting patients with low degrees of astigmatism . While we acknowledge this is not optimal, given close to 70% of Indigenous participants with severe uncorrected refractive error had a cylinder equal to or less than 1 dioptre, there may be a case for spherical lenses that fit frames with standardised apertures to be stocked in Aboriginal Health Services in the most inaccessible regions of Australia and health workers could dispense spectacles using auto‐refraction results.…”
Section: Discussionmentioning
confidence: 97%
“…Third, we did not perform subjective refraction, but rather relied on the refraction from an auto‐refractor. Nonetheless, there is evidence that refractions measured by auto‐refractors can correct vision close to that of subjective refractions . Furthermore, the accuracy of auto‐refractors have been shown to be sufficient for screening purposes .…”
Section: Discussionmentioning
confidence: 99%
“…In recognizing the key element of direct and immediate glasses provision, the benefits of self-refraction, and the potential of nonprofessional team members, our model is similar in spirit to other approaches. 12,28,29 The impact is also similar: rapid improvement in people's ability to achieve their goals and improved quality of life.…”
Section: Original Articlementioning
confidence: 99%
“…In the case of high-level spherical refractive errors, inaccurate self-refraction can occur because self-adjustable spectacles are incapable of correcting astigmatism, while with high-level cylindrical refractive errors, this can occur because the range of correction with this device is limited to −6 to +6 D. 9 , 32 Recently, a study has reported successful results for all types of refractive errors including astigmatism with “Smart Glasses” (S-Glasses; [Treacy MP, Dublin, Ireland]), which are a set of preformed lenses that fit frames with standardized apertures supported by an autorefractometer operated by a nonspecialist health worker. 43 Due to the availability of such alternatives, self-adjustable spectacle technology needs to be improved to meet the needs of a wide range of refractive errors if the load on existing eye-care systems is to be reduced.…”
Section: Self-adjustable Spectaclesmentioning
confidence: 99%